Lower Energy-Adjusted Nutrient Intakes Occur Among Food Energy Under-Reporters With Poor Mental Health - Davison, Karen M.; Araujo Almeida, Vanessa; Gondara, Lovedeep (Frontiers in Nutrition, 2022)
Background: Food energy under-reporting is differentially distributed among populations. Currently, little is known about how mental health state may affect energy-adjusted nutrient intakes among food energy under-reporters. Methods: Stratified analysis of energy-adjusted nutrient intakes by mental health (poor vs good) and age/sex was conducted using data from Canadian Community Health Survey respondents (14-70 years; n=8233) who were deemed as under-reporters based on Goldberg’s cut-offs. Results: Most of the sample were experiencing good mental health (95.2%). Significantly lower energy-adjusted nutrient intakes were found among those with poor mental state by age/gender groups for fibre, carbohydrates, protein, vitamins A, B2, B3, B6, B9, C, and D as well as calcium, phosphorus, potassium, and zinc. All micronutrient intakes, except iron, were significantly lower in females between 51-70 years that reported poor mental health. All B vitamins and minerals, except sodium, differed in males between 31-50 years (all p’s < 0.05). Among females 31-50 and 51-70 years, higher energy-adjusted intakes were reported in those reporting poor mental health for vitamin B9 and phosphorous, respectively (p<0.05). Conclusions: Among food energy under-reporters, poor mental health tends to lower the report of specific of energy-adjusted nutrient intakes, including ones considered critical for mental health. Future research is needed to discern if these differences may be attributed to deviations in accurate report of food intakes or a function of measurement error.